Beyond the Law of Peoples: Revisiting the No Cosmopolitan Conception of Human Rights - Fred H. Lawson (حقوق بشر)
Western discussions of human rights have led to the coalescence of two distinct positions regarding the fundamental, inalienable liberties that citizens should be able to enjoy as a matter of principle. The first, commonly known as the cosmopolitan perspective , asserts that one set of basic human rights is valid for all societies. The other claims that citizens of different societies may possess different sets of human rights, albeit ones that any thoughtful person would acknowledge to be essentially decent and appropriate to the cultural and historical circumstances of the community at hand. Among a great many prominent cosmopolitan theorists, David Held stands out as the most consistent and vociferous champion of a universalist conception of human rights. Arguably the most influential proponent of distinct packages of rights for various social milieux is John Rawls, whose controversial notion of the Law of Peoples explicitly calls on liberal societies to tolerate, if not actually respect, alternative ways in which a minimal cluster of basic rights might be articulated. This paper demonstrates first that these two, generally opposed poles of the debate over human rights have moved much closer to one another than one might expect.